Risk Factors of Microvascular Complications Among Type 2 Diabetic Patients Using Cox Proportional Hazards Models: A Cohort Study in Tabuk Saudi Arabia - Saiyed NS; Yagoub U; Al Qahtani B; Al Zahrani AM; Al Hariri I; Syed MJ; Elmardi ME; Tufail MA; Manajreh M (Journal of Multidisciplinary Healthcare, 2022)
Nasrin S Saiyed,1 Umar Yagoub,1 Bandar Al Qahtani,2 Attiya Mohammed Al Zahrani,3 Ibrahim Al Hariri,4 Meerab Javed Syed,5 Mohammed Elmujtaba Elmardi,6 Muhammad Abdullah Tufail,7 Marwan Manajreh1 1Research Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 2Academic Affairs Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 3Surgery Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 4Family Medicine Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 5Internal Medicine Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 6Cardiology Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia; 7Ophthalmology Department, King Salman Armed Forces Hospital, Tabuk, Saudi ArabiaCorrespondence: Umar Yagoub, Director of Research Department, Research Department, King Salman Armed Forces Hospital, Tabuk, Saudi Arabia, Email mohammedumar2001@yahoo.comPurpose: The burden of type 2 diabetes (T2D) is high in Saudi Arabia, but data related to its complications are limited. This study aimed to determine the incidence of microvascular complications caused by T2D and evaluate the impact of the associated risk factors.Patients and Methods: This retrospective cohort study was conducted at two military hospitals in Tabuk, Saudi Arabia. Data on the socio-demographics, glycaemic profile, blood lipid indices, duration of T2D, and associated microvascular complications were collected from electronic health records and medical files. Descriptive statistics and Cox proportional hazards models were used for data analysis.Results: This study included 1563 T2D patients. The incidence of microvascular complications was 34.3% (95% confidence interval [CI], 32.0– 36.6). Retinopathy was the most common complication (incidence=20.0%; 95% CI, 18.0– 22.0%), while nephropathy was the least common complication (incidence=12.2%; 95% CI, 10.6– 13.8%). Advanced age (≥ 65 years) showed the highest risk of retinopathy (Hazard ratios [HR], 2.86; 95% CI, 2.56– 3.21), neuropathy (HR, 2.70; 95% CI, 2.40– 3.05), and nephropathy (HR, 2.37; 95% CI, 2.12– 2.64) compared with their counterparts. After adjusting for potential confounders, the study found that the significant risk factors for microvascular complications were longer duration (≥ 10 years) of T2D (HR, 5.3; 95% CI, 5.1– 5.6), uncontrolled hypertension (HR, 3.9; 95% CI, 3.3– 4.2), poor glycaemic control (HR, 4.6; 95% CI, 4.3– 5.1), obesity (HR, 2.3; 95% CI, 2.2– 2.6), and dyslipidaemia (HR, 1.6; 95% CI, 1.2– 2.0).Conclusion: Given the high burden of microvascular complications in military healthcare facilities in Tabuk, Saudi Arabia, a context-specific accessible public health program focusing on the promotion of a healthy lifestyle, physical activity, and consumption of a healthy diet, as well as the early diagnosis and management of diabetes, needs to be developed and implemented.Keywords: diabetes, microvascular complications, retinopathy, peripheral neuropathy, nephropathy, Saudi Arabia